Tetraazapentacene constructs: controlling bulk-morphology through molecular dimensionality. Issue 9 (27th November 2017) - Geyer, Florian L.; Koser, Silke; Bojanowski, Maximilian N.; Ullrich, Florian; Brosius, Victor; Hahn, Sebastian; Brödner, Kerstin; Mankel, Eric; Marszalek, Tomasz; Pisula, Wojciech; Hinkel, Felix; Bunz, Uwe H. F.
Abstract : Multi-coreTIPSTAP -constructs of different dimensionality were created via "geometrization" of the monomeric, highly crystalline parent using alkyne linkers. Abstract : Multi-coreTIPSTAP -constructs of different dimensionality were created via "geometrization" of the monomeric, highly crystalline parent using alkyne linkers. Morphological diversity is produced, while the material acceptor strength remains untouched. We establish structure–function relationships as the bulk morphology is predicted from the molecular geometry.